The Basic Principles of Perception of Phenomena in Eastern and Western Folklore - Grigoryan, Vachagan; Arakelyan, Ara; Nazaryan, Ani; Iskandaryan, Naira (Տիգրան Մեծ)
The two main principles of perspective of phenomena are analyzed in the study for the first time. The epic works of European and the Near East are interpreted with the help of comparative, combinative, and historical –investigation methods. In European heroic epics, the privilege is given to spatial dimensions, meanwhile in Eastern epics and in the Bible time recognition is more important. The spatial interpretation of the phenomena and Homer‟s approach to creating the characters is spread upon the European epic works. The characters do not undergo sufficient changes in time; they go out of the process of action just the way they have gone inside. In European works, time is a representation of some his-torical events and is connected with social life changes. In Eastern works the changes connect to the civilization‟s long-lasting time, which refers to one‟s inner world.
Keywords: Philosophy; Folklore